Dysregulated Adaptive Immunity Is an Early Event in Liver Cirrhosis Preceding Acute-on-Chronic Liver Failure - Rueschenbaum, Sabrina; Ciesek, Sandra; Queck, Alexander; Widera, Marek; Schwarzkopf, Katharina; Brüne, Bernhard; Welsch, Christoph; Wedemeyer, Heiner; Zeuzem, Stefan; Weigert, Andreas; Lange, Christian M. (Frontiers in Immunology, 2021)
Acute-on-chronic liver failure (ACLF) is characterized by high levels of systemic inflammation and parallel suppression of innate immunity, whereas little is known about adaptive immune immunity in ACLF. We therefore aimed to characterize the development of the adaptive immune system during the progression of liver cirrhosis to ACLF. Patients with compensated/stable decompensated liver cirrhosis, acute decompensation of liver cirrhosis, or ACLF were recruited from a prospective cohort study. Comprehensive immunophenotyping was performed using high dimensional flow cytometry. Replication of Torque teno (TT) virus was quantified as a marker of immunosuppression. High frequencies of detectable TT virus were observed already in patients with compensated/stable decompensated liver cirrhosis compared to healthy controls (>50% vs. 19%), suggesting relatively early occurrence of immunosuppression in cirrhosis. In line, profoundly reduced numbers of distinct innate and adaptive immune cell populations were observed before ACLF development. These changes were accompanied by parallel upregulation of co-stimulatory (e.g. CD40L, OX40, CD69, GITR, TIM-1) and inhibitory immune checkpoints (e.g. PDPN, PROCR, 2B4, TIGIT) on CD4+ and CD8+ T cells, which again preceded the development of ACLF. On a functional basis, the capacity of CD4+ and CD8+ T cells to produce pro-inflammatory cytokines upon stimulation was strongly diminished in patients with acute decompensation of liver cirrhosis and ACLF. Conclusion: Impaired innate and – in particular – adaptive cellular immunity occurs relatively early in the pathogenesis of liver cirrhosis and precedes ACLF. This may contribute to the development of ACLF by increasing the risk of infections in patients with liver cirrhosis.